2014
DOI: 10.1016/j.immuni.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-2 Is a Direct Receptor for Mannose-Capped Lipoarabinomannan of Mycobacteria

Abstract: Mycobacteria possess various immunomodulatory molecules on the cell wall. Mannose-capped lipoarabinomannan (Man-LAM), a major lipoglycan of Mycobacterium tuberculosis, has long been known to have both inhibitory and stimulatory effects on host immunity. However, the direct Man-LAM receptor that explains its pleiotropic activities has not been clearly identified. Here, we report that a C-type lectin receptor Dectin-2 (gene symbol Clec4n) is a direct receptor for Man-LAM. Man-LAM activated bone-marrow-derived de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(208 citation statements)
references
References 50 publications
8
196
0
2
Order By: Relevance
“…Furthermore, dectin 2-FcRγ complexes are thought to form functional complexes with the related CLR macro phage C-type lectin (MCL) in mice 71 . Mouse dectin 2 also induces the expression of proinflammatory cytokines, such as tumour necrosis factor (TNF), IL-6 and IL-23, as well as anti-inflammatory cytokines IL-10 and IL-2, in response to mycobacterial ManLAM, thereby promoting T H 17 cell responses 67 mouse dectin 2 fails to induce Il1b transcription; however, it does result in the SYK-dependent production of reactive oxygen species and potassium efflux, which activate the NLRP3-caspase 1 inflammasome to process immature pro-IL-1β produced in response to triggering of other PRRs, thereby enhancing T H 17 cell responses 72 . Furthermore, dectin 2 signalling in mouse cells indirectly enhances dectin 1-dependent T H 1 cell responses in response to fungal PAMPs, but it remains to be determined which cytokines are involved in this effect 69,70 .…”
Section: Dectin 2 Promotes T H 17 and T H 2 Cell Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dectin 2-FcRγ complexes are thought to form functional complexes with the related CLR macro phage C-type lectin (MCL) in mice 71 . Mouse dectin 2 also induces the expression of proinflammatory cytokines, such as tumour necrosis factor (TNF), IL-6 and IL-23, as well as anti-inflammatory cytokines IL-10 and IL-2, in response to mycobacterial ManLAM, thereby promoting T H 17 cell responses 67 mouse dectin 2 fails to induce Il1b transcription; however, it does result in the SYK-dependent production of reactive oxygen species and potassium efflux, which activate the NLRP3-caspase 1 inflammasome to process immature pro-IL-1β produced in response to triggering of other PRRs, thereby enhancing T H 17 cell responses 72 . Furthermore, dectin 2 signalling in mouse cells indirectly enhances dectin 1-dependent T H 1 cell responses in response to fungal PAMPs, but it remains to be determined which cytokines are involved in this effect 69,70 .…”
Section: Dectin 2 Promotes T H 17 and T H 2 Cell Responsesmentioning
confidence: 99%
“…Therefore, human dectin 2 is not able to induce T H cell responses by itself, as it only induces the expression of REL-controlled interleukins, such as IL-23p19 and IL-1β, and thereby can only enhance T H 17 cell responses that have been induced by other PRRs, such as dectin 1 (REFS 69,70,77,78). Human dectin 2 has also been shown to induce pro-inflammatory cytokines such as IL-1β and TNF in DCs in response to Mycobacterium bovis bacille Calmette-Guérin (BCG), but whether dectin 2 could induce these cytokines on its own was not investigated, and how this affects T H cell differentiation was not determined 67 . The observed differences between mouse and human dectin 2 signalling might reflect differences in species, DC subsets (bone marrow-derived DCs versus monocyte-derived DCs) or cooperation with other CLRs such as MCL.…”
Section: Dectin 2 Promotes T H 17 and T H 2 Cell Responsesmentioning
confidence: 99%
“…CLRs on dendric cells, such as Dectin-1, Dectin-2 and Mincle, can recognize carbohydrate moieties such as β-(1, 3) glucan and mannose [23,24] on antigens in a Ca 2+ -dependent way and trigger a series of downstream immune responses [25,26]. A recent study indicated DCs treated with zymosan showed significant increase of TNF-α secretion mediated by Dectin-1 receptor, one type of CLRs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Certain carbohydrate structures can have dual effects on dendritic cells and one example is the mannose-capped lipoarabinomannan (Man-LAM) from Mycobacterium tuberculosis. This lipoglycan has the ability to induce both proinflammatory (TNF, IL-6 and IL-12p40) and antiinflammatory (IL-10) cytokines by dendritic cells in a Dectin-2-dependent manner [31]. Lastly, dietaryderived oligosaccharides can directly influence mucosal dendritic cells.…”
Section: Key Pointsmentioning
confidence: 99%